1994
DOI: 10.2307/2132146
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of Diversification in the Federal Courts: Gender Effects in the Courts of Appeals

Abstract: Prior scholarship on the effect of the increasing number of female judges leads to three contrasting sets of expectations. Early writings and views of affirmative-action activists suggested that female judges would be more liberal than male judges. On the other hand, a series of empirical studies suggest that we should expect no gender differences. In contrast to both of these perspectives, several feminist scholars suggest that women will be more liberal only when that position expresses support for full part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 22 publications
3
96
1
Order By: Relevance
“…Songer et al (1994), for example, found that the gender of federal appellate judges did not influence decisions in obscenity or search-and-seizure cases, but female judges favored plaintiffs in employment discrimination cases relative to their male counterparts. Differences are also more likely to be found in cases involving so-called women's issues or in which gender is salient---mostly workplace discrimination and harassment cases (Allen & Wall 1987, Boyd 2013, Boyd et al 2010, Farhang & Wawro 2004.…”
Section: Gendermentioning
confidence: 99%
“…Songer et al (1994), for example, found that the gender of federal appellate judges did not influence decisions in obscenity or search-and-seizure cases, but female judges favored plaintiffs in employment discrimination cases relative to their male counterparts. Differences are also more likely to be found in cases involving so-called women's issues or in which gender is salient---mostly workplace discrimination and harassment cases (Allen & Wall 1987, Boyd 2013, Boyd et al 2010, Farhang & Wawro 2004.…”
Section: Gendermentioning
confidence: 99%
“…This leads to a liberal outcome (Boyd, Epstein, and Martin 2010;Songer, Davis, and Haire 1994). This also lends support to the informational account (Boyd, Epstein, and Martin 2010) and feminist legal theory (Songer, Davis, and Haire 1994) in helping explain female voting and influence on sex discrimination cases.…”
Section: Sex Discriminationsupporting
confidence: 54%
“…In other contexts, influence can be the power of persuasion. This can be seen at the panel level when one or two judges change their vote after listening to another panel member (Boyd, Epstein, and Martin 2010;Songer, Davis, and Haire 1994;Moyer and Tankersley 2012;Moyer and Haire 2015). Finally, persuasion can be seen in an overridden judgement because the judge that overrode the previous decision gave thought to the rationale behind the decision and was not persuaded by his argument, choosing to write their opinion based on a different argument.…”
Section: Influencementioning
confidence: 99%
See 2 more Smart Citations